Methods of Programmable Amplitude of Portable Electrical Stimulator for Multi-channel FES - Setiawan, Rachmad; Arifin, Achmad (JAVA Journal of Electrical and Electronics Engineering, 2016)
Fundamental research about Functional Electrical Stimulation (FES) indicates that FES can be used to rehabilitate motoric system of patient experiencing damage at arrangement of central nerve resulted from cerebrospinal of cord injury (SCI) and also stroke. To generate impulse to human body organ activated by FES is difficult and very complex because of nonlinearity response from neuromuscular system, various response of musculoskeletal system such as having long time delay and fatigue phenomenon (muscle fatigue). Therefore, an open-looped control system is inappropriate to employ. Closelooped control is feasibly appropriate to overcome this constraint in FES appliance to yield accurate impulse generator. Fo r the application of closed-loop control at clinical level, FES system must be designed using portable multi-channel device to pleasant the patient. In this research, the realized FES stimulator is designed by employing a highly linear boost converter circuit using fixed frequency and duty cycle ranging from 0% to 25%, because it yields relatively linear and higher output voltage swing than FES controlled by frequency